Միլիցիայի կազմակերպումը Վանի նահանգում (1915 թ. հոկտեմբեր – 1916 թ. սեպտեմբեր) - Ռուբեն Սահակյան (ՀՀ ԳԱԱ հրատ.)
В начале мая 1915 г. город Ван и большая часть Ванской провинции были освобождены армянскими добровольцами и частями русской армии. По приказу русского командования было сформировано Временное Ванское правление (губернаторство) под руководством видного деятеля армянского освободительного движения А. Манукяна. In early May 1915 the city of Van and most of its province were liberated by Armenian volunteers and units of the Russian army. By the order of the Russian Command the Provisional government of Van (governorship) was formed under the leadership of a prominent figure of the Armenian liberation movement A. Manukyan.
Keywords: History; Modern History; D History